Improvement of Cooperative Empowerment of Smallholder Sugarcane Farmers through the Preparation of Standard Operating Procedures (SOP) - Dwi Aryani Suryaningrum; Mohammad Shodiqin; Anna Kusumawati; Azhari Rizal; Muhammad Mustangin; Ratna Sri Harjanti; Yunaidi Yunaidi (Universitas Muhammadiyah Palembang, 2024)
Cooperatives in carrying out their business processes are guided by applicable regulations and standards. Problems that often occur are generally due to changing regulations or ignorance of applicable regulations. This problem causes the cooperative to not run properly, reflecting inefficient governance. The purpose of the sugarcane farmer empowerment program is to assist and simplify the cooperative administration process by publishing a standard operating procedure book based on farmer practices in the field and applicable regulations. This is in line with realizing one of the missions of LPP Yogyakarta Polytechnic, namely organizing community service in order to disseminate information. This activity was carried out with partners from sugarcane farmers in Sleman who are members of the Sido Makmur Abadi Sugarcane Farmers Cooperative. The activity stages begin with identifying problems in the cooperative administration, followed by problem solving by compiling and publishing the SOP book, and finally disseminating SOP book information through socialization to administrators, supervisors, and sugarcane farmers who are members of the cooperative. The process of assessing the level of understanding of sugarcane farmers before and after socialization The results of empowerment show a significant increase in understanding of the SOP from the initial level of understanding of the SOP of cooperative members only 9.09% to 81.82%. Increased understanding of the SOP is expected to be implemented by sugarcane farmers so that the level of governance and performance of the cooperative becomes better than before.